Successful treatment of Chronic Inflammatory Demyelinating Polyneuropathy (CIDP) in Systemic Lupus Erythematosus (SLE) with oral cyclophosphamide - Jasmin, R.; Sockalingam, S.; Shahrizaila, N.; Cheah, T.E.; Zain, A.; Goh, K.J. (Arnold Publishers (journals now owned by Sage), 2012)
Peripheral neuropathy is a known manifestation of systemic lupus erythematosus. However, the association of primary autoimmune inflammatory neuropathies such as chronic inflammatory demyelinating polyneuropathy (CIDP) with SLE is uncommon. We report a 26-year-old man who simultaneously presented with severe CIDP and photosensitive rash, but was unresponsive to intravenous immunoglobulin infusion and continued to progress. He was found to have underlying SLE and improved with combined corticosteroid and immunosuppressive therapy with oral cyclophosphamide. CIDP with underlying SLE may be more resistant to conventional therapy with IVIG, requiring the addition of other immunosuppressive agents.